Expected near-fault reefogenic traps of hydrocarbons on the slope of the Vysachkivsky-Romodanivsky anticline of the southern near-edge zone of the Dnieper-Donets depression - Oliynyk, O.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
Paleozoic carbonate bodies are perspective traps of hydrocarbons. New reefogenic constructions are predicted on the slope of the Vysachkivsky-Romodanivsky anticline. The obtained results will promote the oil and gas exploration within the Dnieper-Donets depression.